Estudo da produção de ácido clavulânico por Streptomyces clavulígerus em diferentes concentrações de lipídios e de fontes complexas de nitrogênio - Ortiz, Sheila Cristiane Alves (2005)
Clavulanic acid (CA), a secondary metabolite from Streptomyces clavuligerus, is a potent inhibitor of β-lactamases, being formulated by harmaceutical industries with other β- lactams antibiotics to produce drugs that overcome the resistance to antibiotics of many pathogenic bacteria. Studies on culture medium composition, as well as how each component is added to the broth are essential for improving and developing fermentation processes both in obtaining high productivity, as well as in simplifying the separation and purification of the final product. The lipids become an interesting alternative to be used in CA production process, once they constitute a concentrated source of energy slowly assimilated by microorganisms. With relation to the nitrogen source, soybean derivatives, as flours and protein isolates, have been used successfully in the production of CA, by supplying precursors for its biosynthesis; however, the appropriate amount of this nutrient in culture media has not been properly established so far. The general objective of the present work was to study the culture medium composition on the improvement of CA production by S. clavuligerus in bench scale bioreactor, using complex nitrogen sources, and lipids as supplementary carbon source. In preliminary cultivations in shake flasks, the effects of nitrogen source and concentration, using soybean flour and Samprosoy 90NB (soybean protein isolate), were studied. The total nitrogen concentrations of 1.6 and 3.2 g.L-1, and soybean oil concentration of 16, 23 and 30 g.L-1 were tested. The results obtained showed that, when the concentrations of soybean oil and initial soybean flour were 23 g.L-1 and 20 g.L-1, respectively, the CA production obtained was 700 mg.L-1 in 132 hours cultivation, and at pH values above 7.0 the production process was severely harmed. In conventional bioreactor cultivations, under pH control with acid or base addition, all the cultivations were marked by the high CA production and productivity, accompanied by small degradation of the product. The culture medium composition and cultivation conditions that generated best results, concerning CA production, were as follows: 800 rpm, 0.5 vvm and pH 6.8, soybean flour and soybean oil concentrations of 40 g.L-1 and 16 g.L-1, respectively. Under these conditions, a maximum production of 906 mg.L-1 of CA in 84 hours cultivation was obtained.